2012
DOI: 10.1038/pr.2012.97
|View full text |Cite
|
Sign up to set email alerts
|

Variable ventilation enhances ventilation without exacerbating injury in preterm lambs with respiratory distress syndrome

Abstract: Background: as compared with constant respiratory rate (RR) and tidal volume (V T ) during controlled conventional mechanical ventilation (cV), variable ventilation (VV) using the same breath-to-breath minute volume but variable V T and RRs enhances ventilation efficiency in preterm lambs. We hypothesized that if V T was adjusted to target permissive hypercarbia, VV would result in more efficient gas exchange without increasing inflammatory and injurious responses in the lung. Methods: Preterm lambs at 129 d g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 42 publications
1
13
1
Order By: Relevance
“…In addition, different aspects of the pneumonia model, including functional, structural, and ultrastructural features, the inflammatory response, and the potential for translocation of bacteria during mechanical ventilation, were characterized in detail (Additional file 1: Figure S1, Tables S1, S2, and S3). We chose a CV of 30% in V T because this level of variability has been shown to improve lung function [8, 23] and reduce lung damage in direct ARDS in rats [8], as well as other species [9, 2427]. Additionally, controls with i.t.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, different aspects of the pneumonia model, including functional, structural, and ultrastructural features, the inflammatory response, and the potential for translocation of bacteria during mechanical ventilation, were characterized in detail (Additional file 1: Figure S1, Tables S1, S2, and S3). We chose a CV of 30% in V T because this level of variability has been shown to improve lung function [8, 23] and reduce lung damage in direct ARDS in rats [8], as well as other species [9, 2427]. Additionally, controls with i.t.…”
Section: Discussionmentioning
confidence: 99%
“…The use of variable tidal volumes, i.e., variable ventilation, has been shown to improve pulmonary function and reduce lung damage in different experimental models of direct [79] and indirect [8, 10] ARDS. Nevertheless, variable ventilation has not been tested during pneumonia.…”
Section: Introductionmentioning
confidence: 99%
“…Of these, 1,778 were excluded after reading the title and abstract because they did not address the central theme of the study. There were discrepancies in the number of articles (28, 30 (9,10) and 31 (9-11) ) selected by the three examiners. Five other articles were extracted from the references of the articles identified in the electronic search.…”
Section: Resultsmentioning
confidence: 99%
“…(21) In three studies, including an experimental ARDS model induced by oleic acid (26) and a preterm lamb model, (10,27) the variable controlled MV did not improve arterial oxygenation compared with conventional controlled MV. The improvement in gas exchange was also evidenced during variable PSV compared with conventional PSV in ARDS models.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, variability in the respiratory system has been found to be important for cell activity, as it positively modulates surfactant secretion [44, 45]; it is also related to the maturation of breathing control in infants [46, 47] and correlates with weaning success [4850]. Animal studies have shown that variability improves ventilation efficiency and lung compliance in the preterm lung without increasing lung inflammation or lung injury [51, 52]. …”
Section: Ventilation Modesmentioning
confidence: 99%